The Influence of Digitalization on Integrated Logistics Management in Contemporary Port Operations - Arif Rachman Dillah; Haidar Rizqi Lumintu; Fakhri Najmuddin; Kencana Verawati (Global Leadership Organizational Research in Management, 2025)
Digitalization has become the driving force behind transformation in the logistics sector, particularly at seaports, which serve as key nodes in the global supply chain. Indonesian ports face persistent challenges such as high logistics costs and long vessel turnaround times. By implementing digital technologies such as the Port Community System (PCS), Artificial Intelligence (AI), and Blockchain, ports can enhance operational efficiency, accelerate service processes, and improve transparency and accountability. Digital systems also enable real-time integration among stakeholders, contributing to faster cargo flow and reduced national logistics costs. However, the implementation of digitalization is not without significant barriers, including limited information and communication technology (ICT) infrastructure, low digital competencies among the workforce, and high initial investment costs. Furthermore, ports face organizational cultural resistance to change and cybersecurity risks that threaten operational continuity. Smaller ports in developing countries often struggle to adopt these technologies independently due to budget constraints. To overcome these challenges, synergy between the government, port operators, and technology providers is essential. Programs such as the National Logistic Ecosystem (NLE) represent a strategic step to accelerate sustainable digital adoption. With a holistic approach encompassing technology, human resources, and business processes, digitalization can become a key catalyst in enhancing the competitiveness of Indonesian ports on a global scale.